ИЗВЛЕЧЕНИЕ СОЕДИНЕНИЙ ЛИТИЯ ИЗ ЖИДКИХ ИСТОЧНИКОВ - Абдуллаев Бахoдир; Усманов, Илхам; Махмаёров, Жасур; Самадий, Муроджон (Theoretical and experimental chemistry and modern problems of chemical technology, 2023)
The article provides information on methods for separating lithium from aqueous solutions. It is shown that one of the promising methods is adsorption. Information is provided on sorbents used in the adsorption extraction of lithium.